PARA AS NOVAS GERAÇÕES: A ATUALIDADE DA SOCIOLOGIA CRÍTICA - Carvalho, Mônica de (GEOUSP Espaço e Tempo (Online), 2005)
Post-modern critic has questioned the production of objective knowledge in the human sciences, thus rendering unviable the possibility of critical interpretation of contemporary society. In view of the emergence of different historical senses, the contemporary intellectual, given the contradictions imposed by capitalist society, has forsaken his public role of highlighting the possibilities of overcoming an eternal present, resigning himself to moral relativism, which rather contributes to keep imprisoned the subjects who should have been released with the criticism of scientificism and of the domination of instrumental reason. This paper intends to problematize such issues and show the need to bring back into debate the role of intellectuals in contemporary society, as well as the relevance of critical thinking.